Analisis Penerapan Metode Ahp Dan Borda Untuk Kawasan KPHP (Kesatuan Pengelolaan Hutan Produksi) Sungai Sembulan Bangka Tengah - Fitriyani, F; Andrika, Yuyi (LPPM STIKOM Tunas Bangsa, 2024)
The KPHP Sungai Sembulan area is a region with significant potential for production forests, and as such, it is protected by law. As a production forest, this area yields both timber and non-timber forest products. It is crucial to protect this area due to frequent instances of irresponsible forest management by certain individuals. The production forest products are often traded illegally, and the forest land is sometimes used irresponsibly for unconventional mining activities. Therefore, a system is needed to identify the best KPHP Sungai Sembulan area, which is one that has good forest management practices. This research employs the AHP (Analytical Hierarchy Process) method to determine the weights of multiple criteria and alternatives, and the Borda method to perform voting on the alternatives derived from the AHP results. The purpose of this study is to develop a system that can assess the potential of KPHP areas in Sungai Sembulan, so the system can recommend the best KPHP areas. These areas could then become a government target for self-sufficient KPHP areas in terms of income and management. The results of the research show that Keretak has the highest weight of 0.223684211, followed by Lampur and Kerantai with a weight of 0.210526316, Kemingking with a weight of 0.184210526, and Tanjung Pura with a weight of 0.171052632.